Improving the cellular invasion into PHEMA sponges by incorporation of the RGD peptide ligand: The use of copolymerization as a means to functionalize PHEMA sponges - Paterson, S.; Shadforth, A.; Shaw, J.; Brown, David; Chirila, T.; Baker, M. (Elsevier Science, 2013)
A monomer that contained the RGD ligand motif was synthesized and copolymerized with 2-hydroxyethyl methacrylate using polymerization-induced phase separation methods to form poly(2-hydroxyethyl methacrylate)-based hydrogel sponges. The sponges had morphologies of aggregated polymer droplets and interconnected pores, the pores having dimensions in the order of 10 µm typical of PHEMA sponges. RGD-containing moieties appeared to be evenly distributed through the polymer droplets. Compared to PHEMA sponges that were not functionalized with RGD, the new sponges containing RGD allowed greater invasion by human corneal epithelial cells, by advancing the attachment of cells to the surface of the polymer droplets.